Complex Acoustic Gravity Wave Behaviors to a Mathematical Model Arising in Nonlinear Mathematical Physics - Akturk, Tolga; Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet; Bulut, Hasan (E D P Sciences, 2018)
In this article, we utilize the powerful sine-Gordon expansion method (SGEM) in constructing some new solutions to the (2 + 1)-dimensional Boiti-Leon-Pempinelli equation by using the Mathematica software. We successfully obtain some new travelling solutions bearing some new structures such as trigonometric function, exponential function and hyperbolic function structures. We claim that some of our results are complex in structure. All the solutions obtained verified the the (2 + 1)dimensional Boiti-Leon-Pempinelli equation. To illustrate our results, present the numerical simulation of all the obtained solutions in this study by selecting appropriate values of the parameters. Furthermore, we give the physical interpretation of all the graphics. We also give the physical meaning to some of the obtained results in this study.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Soliton-Solutions